On-Campus Internships at Binghamton University, State University of New York - Wandell, Christopher; Martin, Michael (Experiential Learning and Teaching in Higher Education, 2025)
Internships are educationally powerful practice-runs for the world of work and civic participation after college. But in too many cases these experiences are out of reach, for the students whose off-campus responsibilities – or just transportation challenges – get in the way. Learn how SUNY Binghamton extends the reach of this high-impact practice, and hear directly from students about the benefits.